Student loans as symbolic violence. Issue 2 (4th March 2021) - Harris, Diane; Vigurs, Katy; Jones, Steven
ABSTRACT: This paper asks whether Bourdieu's notion of symbolic violence is a helpful lens through which to view student loan systems. Symbolic violence occurs when two unequal agents unconsciously conspire in the oppression of the less empowered agent, thus reinforcing and legitimating existing stratifications. Using England as a case study, we draw on in-depth interviews with 74 graduating students at two types of university. Half of the interviewees were part of a lower fees (pre-2012 entry) cohort and half were part of a higher fees (2012 entry) cohort. Students share ways in which the loan system affects their psychological stability and their imagined futures. We argue that symbolic violence (a) is encoded in public discourses of student borrowing; (b) becomes more prominent as systems move towards higher fees, regardless of forecast total repayment levels; and (c) is experienced differently by different types of students.